Cloning and Efficient Expression of Bacillus sp. BH072 tasA Gene in Escherichia coli - 韩烨 樊洁 周志江 檀茜倩 赵鑫 (Transactions of Tianjin University, 2015)
The Bacillus strain BH072 isolated from a honey sample showed strong antifungal activity against phytopathogen. Gene cloning test demonstrated that the strain had a tasA gene encoding an antifungal TasA protein. Although the wild strain simultaneously produced various antifungal substances, only the physicochemical property and antifungal activity of TasA protein were unclear due to the difficulty in extraction. In this study, tasA gene encoding the protein from Bacillus sp. BH072 was amplified by using the polymerase chain reaction （PCR） method and cloned into pET 28a （＋） vector, and then expressed in host cells Escherichia coli BL21 （DE3）. The expressed proteins were collected by centrifugation and ultrasonic treatment, and then purified by using nickel-nitrilotriacetic acid （Ni-NTA） metal affinity column and dialysis methods. The result of sodium dodecyl sulfate-polyacrylamide gel electrophoresis （SDS-PAGE） test showed that an expected protein band appeared with a size of 31 kDa. The expressed products possessed antifungal activity against the phytopathogenic indicator strain Botrytis cinerea. A genetically engineered strain tasA orE, coli was established in this study which can efficiently express Tas A protein.